Modeling of the Wear Process of a Locomotive Wheelset and Rail During Sliding in a Curve - Afanasov, A. M.; Holik, S. M.; Buriak, S. Y.; Kravchunovskyi, O. H.; Fedorov, Y. F.; Gololobova, O. O. (Science and Transport Progress, 2023)
Purpose. This article is aimed at analyzing the wear process of locomotive wheelset and rail bands in curved sections of the rail track using the formalization of the ridge wear indicator for the wheelset slippage cycle. Methodology. In the process of developing a model for the wear of a locomotive wheelset, the phenomenon of slippage during the realization of traction torque was considered and the sliding speed functions at the point of contact between the wheel and the rail were determined. On the basis of the obtained functions, an analytical expression for determining the wear factor of the rims and ridges is proposed. To simplify practical calculations, the concept of the relative wear rate of the wheel ridge is introduced and an analytical expression for its determination is proposed. Findings. Our studies show that the slippage of locomotive wheelsets during the realization of traction torque is one of the decisive factors that determines the wear of the ridges. A significant reduction in the resulting ridge slip during slippage can be achieved by reducing the response time of anti-skid devices. It should also be noted that the resulting slip decreases to a greater extent than the speed of the snowplow protection increases. Originality. In this study, for the first time, a model of the wear process of wheel set tires and rims during locomotive slippage is proposed in a curve, where the wheel rim wear factor is represented as the total work of friction forces per slippage cycle. Practical value. The proposed analytical model can be used to predict the service life of locomotive wheel sets and to standardize train weights on railroad sections with a complex track plan and profile.